Antecedent Metabolic Health and Metformin (ANTHEM) Aging Study: Rationale and Study Design for a Randomized Controlled Trial. Issue 12 (2nd December 2021) - Kumari, Santosh; Bubak, Matthew T; Schoenberg, Hayden M; Davidyan, Arik; Elliehausen, Christian J; Kuhn, Katrin G; VanWagoner, Timothy M; Karaman, Rowan; Scofield, Robert Hal; Miller, Benjamin F; Konopka, Adam R
Abstract: The antidiabetic medication metformin has been proposed to be the first drug tested to target aging and extend healthspan in humans. While there is extensive epidemiological support for the health benefits of metformin in patient populations, it is not clear if these protective effects apply to those free of age-related disease. Our previous data in older adults without diabetes suggest a dichotomous change in insulin sensitivity and skeletal muscle mitochondrial adaptations after metformin treatment when co-prescribed with exercise. Those who entered the study as insulin-sensitive had no change to detrimental effects while those who were insulin-resistant had positive changes. The objective of this clinical trial is to determine if (a) antecedent metabolic health and (b) skeletal muscle mitochondrial remodeling and function mediate the positive or detrimental effects of metformin monotherapy, independent of exercise, on the metabolism and biology of aging. In a randomized, double-blind clinical trial, adults free of chronic disease ( n = 148, 40–75 years old) are stratified as either insulin-sensitive or resistant based on homeostatic model assessment of insulin resistance (≤2.2 or ≥2.5) and take 1 500 mg/day of metformin or placebo for 12 weeks. Hyperinsulinemic-euglycemic clamps and skeletal muscle biopsies are performed before and after 12 weeks to assess primary outcomes of peripheral insulin sensitivity and mitochondrial remodeling and function. Findings from this trial will identify clinical characteristics and cellular mechanisms involved in modulating the effectiveness of metformin treatment to target aging that could inform larger Phase 3 clinical trials aimed at testing aging as a treatment indication for metformin. Clinical Trials Registration Number : NCT04264897.